Development and validation of a multi-substance method for routine analysis of pesticides in post-mortem samples by UPLC-MS/MS - Matos, Francisco (2023)
Pesticides play an important role in forensic toxicology and are usually classified as a single class of chemicals, but in fact there are several different types of compounds, including organophosphates, carbamates, pyrethroids or organochlorines, among others, with different toxicities. Pesticide analysis in post-mortem samples can be difficult due to the complexity of the samples and to the high toxicity of these compounds. The aim of this study was to develop and validate an easy to use, sensitive, and robust method, using ultra-performance liquid chromatography-tandem mass spectrometry to be incorporated in the routine flow for more than fifty pesticide analysis in post-mortem blood. The developed analytical method was fully validated according to the guiding principles of the ANSI/ASB Standard 036 and applied to routine post-mortem samples, being already detected more than 15 positive cases. This UPLC-MS/MS method is useful and a powerful tool in a toxicology lab because it is fast, simple, effective, and trustworthy. This method is able to detect and analyse pesticides in post-mortem samples. It is set to use for routine analysis and successfully applied to intoxication cases.